E-Learning Berbasis Web Pada Ma Negeri 2 Tanjung Jabung Timur - Saudina , Mira; Yaakub, Saleh (Jurnal Manajemen Sistem Informasi, 2022)
There are several problems that occur at MA Negeri 2 Tanjung Jabung Timur so far the teaching and learning process between teachers and students is very limited. So if there are obstacles, such as students who do not understand certain subject matter, it will be difficult if they want to repeat the material and ask the teacher concerned directly. The face-to-face learning process in the classroom sometimes makes students bored because they are too tired with the monotonous learning system and at times. Covid-19 pandemic students at MA Negeri 2 study at home by being given assignments by the teacher where the assignments are taken at school and then collected again with the time that has been given by the teacher for each subject which causes the teaching and learning process to be ineffective. This research is website-based e-learning. The purpose of this study was to analyze and design a website-based e-learning system at MA Negeri 2 Tanjung Jabung Timur. The system modeling tools used are UML (Unified Modeling Language) and Balsamiq Mockups 3 to design prototypes. Based on the results of research on the analysis and design of the learning system at MA Negeri 2 Tanjung Jabung Timur, it is currently still less effective and efficient because it uses conventional learning media, so a website-based e-learning system is needed that has the features needed to support the teaching and learning process without being constrained by space. and time. Suggestions for this research are expected that further research can design an e-learning system with achievement features.